Cultural Tourism at the Gelora Bung Karno Main Stadium - Aditya Erlangga; Rizki Nurul Nugraha (West Science Information System and Technology, 2024)
Cultural tourism needs to be preserved as it can be a forum for future generations to continue to learn about local traditions and cultures amid rapid technological advances. Researchers use this title to identify the potential of cultural tourism at the Gelora Bung Karno Main Stadium (SUGBK). SUGBK was chosen as a locus because it is an important cultural landmark in Jakarta with various art and cultural activities. This research uses qualitative methods, with a qualitatively descriptive approach. Data collection is done through field surveys, interviews and literature studies. The need of this research is to explore the potential and impact of SUGBK cultural tourism on social, economic and cultural aspects. Socially, the stadium is a means of cross-cultural interaction and enriches people's insights. Economically, tourism creates business opportunities such as street sellers and souvenir sellers around the stadium. Meanwhile, from a cultural point of view, the various traditional art performances held at the stadium helped preserve the ancestral heritage.